2018
DOI: 10.1007/s10461-018-2155-9
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Social Desirability Bias: Investigating Inconsistencies in Self-Reported HIV Testing and Treatment Behaviors Among HIV-Positive Adults in North West Province, South Africa

Abstract: This mixed-methods study used qualitative interviews to explore discrepancies between self-reported HIV care and treatment-related behaviors and the presence of antiretroviral medications (ARVs) in a population-based survey in South Africa. ARV analytes were identified among 18% of those reporting HIV-negative status and 18% of those reporting not being on ART. Among participants reporting diagnosis over a year prior, 19% reported multiple HIV tests in the past year. Qualitative results indicated that particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…First, information on HIV testing in the past year is not used in model calibration due to evidence that this likely overstates the true annual testing rate [14,35] , perhaps due to "telescoping bias" in which respondents may inadvertently recall testing that occurred beyond the last 12 months [36] (see supplemental materials, Text S3). Second, information on self-reported awareness of HIV-positive status, even when partially adjusted for detection of ART among PLHIV who report not knowing their status, is not incorporated due to evidence of systematic nondisclosure of knowledge of status [9,10,[37][38][39][40][41][42][43][44] . In particular, non-disclosure of HIV status was found to be 1.4 times higher among individuals not on ART in Mozambique [38] compared to those on ART.…”
Section: Data Sources Likelihood Function and Model Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…First, information on HIV testing in the past year is not used in model calibration due to evidence that this likely overstates the true annual testing rate [14,35] , perhaps due to "telescoping bias" in which respondents may inadvertently recall testing that occurred beyond the last 12 months [36] (see supplemental materials, Text S3). Second, information on self-reported awareness of HIV-positive status, even when partially adjusted for detection of ART among PLHIV who report not knowing their status, is not incorporated due to evidence of systematic nondisclosure of knowledge of status [9,10,[37][38][39][40][41][42][43][44] . In particular, non-disclosure of HIV status was found to be 1.4 times higher among individuals not on ART in Mozambique [38] compared to those on ART.…”
Section: Data Sources Likelihood Function and Model Calibrationmentioning
confidence: 99%
“…There are few empirical estimates of awareness status among PLHIV and, as described above, these estimates are likely to reflect substantial underreporting of HIV awareness [9,10,[37][38][39][40][41][42][43][44] . We therefore validated the F90 model by performing both in-sample comparisons (A) and out-ofsample predictions (B and C) of the proportion of the population ever tested for HIV (stratified by sex and HIV status).…”
Section: Model Validationmentioning
confidence: 99%
“…There may also be a social desirability bias present: patients are not inclined to declare their non-adherence to a healthcare professional. 13 This bias may have led patients to give negative responses in the face-to-face interview simply to avoid judgment by a healthcare professional. In the future, it may be interesting to investigate the extent of the social desirability bias in face-to-face interviews that use the MAQ.…”
Section: Discussionmentioning
confidence: 99%
“…In this stigmatized group, the fear of discrimination and lack of trust towards health care workers could certainly be driving some of the misreporting. However, poor understanding of HIV care from PWID may have also played a role [20]. To overcome these difficulties, it was suggested that: (i) questionnaires could be administrated by peers, (ii) and run outside the health service system and (iii) data should come from population-based surveys [15].…”
Section: Discussionmentioning
confidence: 99%
“…Using the same design, i.e. comparing selfdeclaration of HIV testing and plasma ARV detection, they found that the level of discrepancies ranged from 18% to 41% [20,26]. Among the factors associated with misreporting, they identified "being a man" as a positive risk.…”
Section: Discussionmentioning
confidence: 99%